Perceived Barriers to the Consumption of Fruits and Vegetables in Middle Age: Qualitative Ecological Study - Bagheri , Sharareh; Ezzati Rastegar , Khadije; Setayesh, Aysan (Shahroud Journal of Medical Sciences, 2021)
Background: Consumption of fruits and vegetables is associated with reduced occurrence of mortality stemming from a variety of chronic diseases. This study, employing the environmental model of health behaviors, aimed to investigate the perceived barriers to the consumption of fruits and vegetables in middle-aged individuals.Methods: This is a qualitative study of content analysis, conducted through eight focus group discussions targeting middle-aged individuals, and five individual interviews with the key individuals in 2017. A framework of factors altering the nutritional behaviors of individuals who were classified into four levels was recognized via employing the ecological model. Results: Barriers to consuming fruits and vegetables at the individual level included beliefs, nutritional awareness, and eating habits of the past. At the interpersonal level, family and social support were the major barriers. At the community level, socio-cultural values ​​and norms, environmental components such as accessibility, quality of fruits and vegetables, media, and prices were also among the major barriers. At the public policies level, not monitoring the production and supply of quality products were among the barriers the participants stated.Conclusions: Politicians should weigh upon support programs to reduce the production cost of high-quality fruits and vegetables in low-income communities, and adopt the necessary laws and policies to discuss the production and supply of quality, toxin-free fruits, and vegetables at the macro level.Keyword: Fruits, Vegetables, Ecological model, Qualitative study, Focus group